IMPLEMENTASI MODEL KONSELING CALM CORNER DALAM MEMBANTU PERKEMBANGAN EMOSIONAL ANAK USIA DINI - Rina Hizriyani; Alda Thalia Salsabila (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2025)
Emotional development is an important aspect of human development, including in early childhood. Emotional development in young children refers to their ability to recognize and express their feelings toward themselves and others. To support appropriate emotional development, teachers can employ various methods to facilitate the developmental process. One method that can be used is the Calm Corner counseling model, also known as a quiet corner for children. This study employed a qualitative research method aimed at examining the implementation of the Calm Corner counseling model in supporting the emotional development of young children in Group A at TK Aisyiyah Bustanul Athfal Tengah Tani. The subjects of the study consisted of six children. The results showed that all six children initially experienced difficulties in emotional development. However, their emotional development gradually improved after the implementation of the Calm Corner in the classroom. This improvement was reflected in the final results, which showed an increase in the percentage of children who demonstrated emotional development. Initially, none of the children (23%) were able to demonstrate the expected emotional development independently. After the implementation of the Calm Corner, this percentage increased to 83%. Meanwhile, the percentage of children who were able to demonstrate the expected emotional development with assistance decreased from 83% to 17%. Children who were previously unable to demonstrate the expected emotional development subsequently became able to do so with assistance. Therefore, the findings of this study indicate that the Calm Corner can be used as an alternative strategy to support the emotional development of young children.